Pendekatan Restorative Justice Dalam Penyelesaian Konflik Antar Negeri Di Saparua - Manawan, Edgar Erlangga; Pasalbessy, John Dirk; Hattu, Jacob (Faculty of Law, Universitas Pattimura, 2024)
Introduction: Indonesia in handling conflicts in general is mostly resolved by using the concept of a customs approach: Like the conflict in the Saparua Archipelago, the conflict between Haria and Porto took place from 2011 to 2013, conflicts caused by Boundary Disputes in Air Raja, and brawls school children involving students from Negeri Haria and students from Negeri Porto.Purposes of the Research: This writing aims to find out how the Restorative Justice Approach Process is carried out by the Saparua Police in resolving interstate conflicts in Saparua, as the aim of which is to find out what are the benefits and obstacles encountered in implementing the restorative justice approach.Methods of the Research: This research method is empirical juridical research and uses a sociological approach with the community, data collection techniques through interviews and documents obtained from the library and the authorities, data processing techniques, namely by editing to find out that the data collected is sufficient good or not in supporting problem solving, Data Analysis Method uses qualitative analysis techniques.Results of the Research: The results of the study show that the restorative justice approach applied to social conflicts in Saparua countries is very good and in accordance with the traditional customs of the Saparua people in resolving conflicts, and with the existence of a restorative justice approach it provides certainty of justice for victims, perpetrators and society and conflict resolution is recognized in the eyes of the law because it is a mechanism of the criminal justice system.